Transmissible Diseases, Vaccination and Inequality - Carmen Camacho; Chrysovalantis Vasilakis (Institute of Labor Economics (IZA), 2023)
We build a Susceptible-Infected-Vaccinated Economic two-sector growth model to study the evolution of inequality in an economy with two groups of workers, who are differently exposed to a transmissible disease. We show that the economy can lead to various scenarios in the long run, which range from a disease-free economy to a scenario in which only the most exposed group suffers from the virus. Our numerical exercises show that the question of how a transmissible disease affects long-run inequality depends on the economic variable we use to build our inequality measure, on the infectiousness of the disease, and on whether we address individual or group measures of inequality. Under our calibration, if the share of vaccinated trespasses the 24%, then the effect of the disease on inequality in capital assets is not monotone in the exposure rate.
Keywords: C6; I14; 330; inequality; transmissible disease; vaccination